"Just Be There": Desired Partner Behaviors Among Pregnant People Living With Opioid Use Disorder, a Qualitative Study. Issue 6 (8th November 2022) - Sack, Daniel E.; Sheridan, Maria E.; Audet, Carolyn M.
Abstract : Objectives: Elicit how partners impact pregnant peoples experience living with opioid use disorder (OUD) during pregnancy and summarize participant recommendations to improve partner support from people engaged in treatment for OUD during pregnancy. Methods: In this qualitative study, we completed 20 in-depth interviews in pregnant people with OUD at an outpatient clinic in Tennessee. We employed inductive and deductive coding based on a relationship intimacy model and thematic analysis to elicit the perspectives, attitudes, and experiences that shaped desired partner behaviors during their pregnancy. We placed our findings in a modified relationship intimacy model of couple adaptation to OUD. Finally, we summarized interviewed participants' recommendations on how to best educate and involve their partners. Results: Our analysis generated 24 codes and 5 themes. Previous lived experience and interpersonal factors influenced participants' experiences with relationship-compromising and relationship-enhancing behaviors. They also reported that positive, or relationship-enhancing behaviors, could mitigate some of their negative intrapersonal feelings such as self-stigma. Participants agreed that partners should display emotional intelligence and empathy, provide supportive logistic and physical behaviors, and be open to improve. Participants also suggested that partners be equipped with information about expected physiological changes during pregnancy, supportive behavior examples, and information about OUD treatment. Conclusions: Additional input from pregnant people and partners in future projects can build on these findings and guide the creation and assessment of comprehensive interventions to improve care for pregnant people with OUD.